Evaluate of head loss, sediment value and copper removal in sand media (rapid sand filter) - Navab, Daneshi; Hossein, Banejad; Reza, Pirtag Hamedany; Vahab, Daneshi; Maedeh, Farokhi (International Journal of Environment, 2014)
Along with the technology development and increasing consumption of water resources, we are experiencing low qualities in the mentioned resources. Copper brings about serious environment al pollution, threatening human health and ecosystem. This metal found variously in water resources and industrial activities. Therefore, it needs to treat the water resources from these excessive amounts. Different methods have used for this reason but the most used method during recent years has been the absorption by economic absorbers such as sand. Rapid sand filters usually used in water and wastewater treatment plants for water clarification. In this research, a single layer gravity rapid sand filter has used to reduce different concentrations of copper. sediment value and head loss arising in filter media is simulated by using combination of Carman-Kozeny, Rose and Gregory models in different discharges of rapid sand filter. Results have shown that with increasing in discharge and decreasing in input copper concentration, arriving time to given head loss, is increasing. In addition, results demonstrated that with increasing in copper concentration in influent, removal efficiency is decreasing somewhat. Results of this research can applied in an appropriate design of rapid sand filter to copper removal, a prediction of rapid sand filter ability to copper removal and an estimation of arising head loss during filter work thus evaluating of time interval backwash. DOI: http://dx.doi.org/10.3126/ije.v3i2.10641 International Journal of the Environment Vol.3(2) 2014: 276-286